Online Learning Using Audio Visual Media Through WhatsApp Class I Students Elementary School: Pembelajaran Daring Menggunakan Media Audio Visual Melalui WhatsApp Siswa Kelas I MI - Indah Wahyuni; Nur Maslikhatun Nisak (Universitas Muhammadiyah Sidoarjo, 2021)
During the current COVID-19 pandemic, learning that is carried out in elementary schools and madrasas iftidaiyah is online learning. The purpose of this research is to find out how the implementation of online learning using audio-visual media through WhatsApp Class I MI Nurul Huda Ngampelsari and to find out what obstacles occur in online learning Class I MI Nurul Huda Ngampelsari. This research method uses descriptive qualitative method with the main data sources and supporting data. The main data sources as research subjects were first grade teachers, madrasa principals, parents, and grade I students at MI Nurul Huda Ngampesari. Data collection techniques by conducting observations, interviews and documentation. While the data analysis and interpretation techniques used data collection techniques, data reduction, data presentation, and conclusions and data verification. From the research conducted, it was found that the learning carried out in Class I MI Nurul Huda Ngampelsari was carried out online. As well as the use of audio-visual media for online learning such as: learning videos made by class teachers or those taken by YouTube, voice messages or voice notes and using WhatsApp to send materials and assignments. In addition to using WhatsApp, the teacher also uses several kinds of applications, lesson plans, and written assignments in the form of worksheets that are collected once a month to see student activity in doing assignments. There are several obstacles in online learning, including data packages for students, the lack of enthusiasm of students in participating in online learning, and the lack of parental roles in assisting children in participating in online learning.